2008
DOI: 10.1021/np070452q
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Constituents of the Red Alga Gracilaria verrucosa and Their Synthetic Analogues

Abstract: A chemical study on the anti-inflammatory components of the red alga Gracilaria verrucosa led to the isolation of new 11-deoxyprostaglandins ( 1- 4), a ceramide ( 5), and a C 16 keto fatty acid ( 6), along with known oxygenated fatty acids ( 7- 14). Their structures were elucidated on the basis of NMR and MS data. The absolute configurations of compounds 1- 5 were determined by Mosher's method. The anti-inflammatory activity of the isolated compounds ( 1- 14) was evaluated by determining their inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 56 publications
(183 reference statements)
5
53
0
1
Order By: Relevance
“…Carrageenan was shown to stimulate the generation of superoxide, PMNs, and the secretion of TNF-α from macrophages (Shibata et al 2000). Similarly, there are reports about constituents of the red alga Gracillaria verrucosa that indicate its anti-inflammatory activity determined by their inhibitory effects on the production of the same pro-inflammatory mediators (NO, IL-6, and TNF-α; Dang et al 2008). Our results, however, do not agree with this observation; in fact, the polysaccharides from Hy.…”
Section: Discussionmentioning
confidence: 96%
“…Carrageenan was shown to stimulate the generation of superoxide, PMNs, and the secretion of TNF-α from macrophages (Shibata et al 2000). Similarly, there are reports about constituents of the red alga Gracillaria verrucosa that indicate its anti-inflammatory activity determined by their inhibitory effects on the production of the same pro-inflammatory mediators (NO, IL-6, and TNF-α; Dang et al 2008). Our results, however, do not agree with this observation; in fact, the polysaccharides from Hy.…”
Section: Discussionmentioning
confidence: 96%
“…We previously showed that depleting activated macrophages and TAMs can reduce angiogenesis or lymphangiogenesis and tumor growth, which is closely associated with inflammatory stimuli (10)(11)(12)33), suggesting that natural anti-inflammatory compounds can suppress not only inflammatory signaling but also VEGFinduced angiogenesis. Dang et al developed anti-inflammatory enone fatty acids, including C10, by screening for the inhibition of NO, TNF-· and IL-6 production in stimulated macrophages (13). The enone fatty acid induced apoptosis and inhibited DNA synthesis in human cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Dang et al isolated anti-inflammatory agents from red alga for the development of novel therapeutic drugs for inflammatory diseases (13). They showed that new prostaglandins and oxygenated fatty acids isolated from the red alga, Gracilaria verrucosa, inhibited the production of major mediators of inflammation, including nitric oxide (NO), IL-6 and TNF-·, in lipopolysaccharide (LPS)-activated RAW264.7 cells (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of antibiotic, anti-HIV, anticoagulant, anticonvulsant, anti-inflammatory (Dang et al, 2008), antineoplastic, wound healing, antiulcer (Nagaoka et al, 2000), hepatoprotective (Mosaad et al, 2006) and antitumor activities for seaweed derived compounds have been reported (Lincoln et al, 1991). Seaweeds also assumed greater significance as they are rich sources of various types of antioxidant compounds (Kuda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%